High-Dose-Rate Interstitial Brachytherapy (Interventional Radiotherapy) for Conjunctival Melanoma with Orbital Extension - Pagliara, Monica Maria (Ocul Oncol Pathol, 2021)
PURPOSE: To evaluate local control and functional and cosmetic outcomes of postoperative high-dose-rate interventional radiotherapy (HDR-IRT) in patients affected by conjunctival melanoma with orbit invasion. METHODS: A retrospective study was conducted in 2 patients affected by conjunctival melanoma infiltrating the orbit, treated with surgical excision and HDR-IRT. The treatment procedures consisted of surgical excision of the orbital infiltrating nodule followed, 1 month after surgery, by adjuvant HDR-IRT. A target dose of 34 Gy was delivered in 10 twice-a-day fractions over 5 consecutive days. Data analysis included local tumor control and metastatic rate, acute and late toxicity, functional and aesthetic results. RESULTS: In both patients, treatment was well tolerated, and there was no orbital recurrence at a median follow-up of 37–40 months. There was an excellent functional outcome, without no significant acute or late side effects. CONCLUSIONS: HDR-IRT could be considered a promising, feasible, successful, and well-tolerated option for selected patients affected by ocular tumors with orbital invasion.